2000
DOI: 10.1002/1098-2388(200007/08)19:1<36::aid-ssu6>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Surgical staging of early invasive epithelial ovarian tumors

Abstract: Early stage epithelial ovarian carcinoma is defined pathologically as a tumor strictly limited to one or both ovaries without any extra‐ovarian disease (i.e., Stage IA or B of the International Federation of Gynecology and Obstetrics (FIGO) classification). This diagnosis can be obtained only after an exhaustive surgical staging procedure, performed as soon as the diagnosis of epithelial invasive ovarian carcinoma is established. This staging surgery currently encompasses a peritoneal cytology, the thorough in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 38 publications
1
19
0
4
Order By: Relevance
“…In early stage ovarian cancer, multiple studies have demonstrated feasibility and efficacy of complete laparoscopic staging. 414 Laparoscopy offers several advantages to traditional open surgery: optical magnification of abdominal and pelvic anatomy, ease in visualization of the diaphragm and peritoneal surfaces, shorter postoperative recovery, and a decrease in length of hospital stay. 4 In advanced stage ovarian cancer, the role of laparoscopy has been described as a tool to triage for resectability and second-look evaluations, with limited studies on its role in cytoreductive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In early stage ovarian cancer, multiple studies have demonstrated feasibility and efficacy of complete laparoscopic staging. 414 Laparoscopy offers several advantages to traditional open surgery: optical magnification of abdominal and pelvic anatomy, ease in visualization of the diaphragm and peritoneal surfaces, shorter postoperative recovery, and a decrease in length of hospital stay. 4 In advanced stage ovarian cancer, the role of laparoscopy has been described as a tool to triage for resectability and second-look evaluations, with limited studies on its role in cytoreductive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Les stadifications des tumeurs frontières et malignes sont également insuffisantes et l'on peut regretter les 8 % de rupture accidentelle de tumeurs malignes [22]. Toutes les recommandations insistent sur la nécessité de cette stadification [4,[23][24][25]. Cette observation est d'autant plus surprenante que les opérateurs avaient une bonne appréciation du risque de malignité.…”
Section: Discussionunclassified
“…Leblanc et al ont rapporté leur expérience concernant la chirurgie de restadification des tumeurs de l'ovaire a priori de stade I [17]. Leurs résultats semblent suggérer que cette chirurgie de restadification (incluant la lymphadénectomie pelvienne et lomboaortique) est réalisable par coelioscopie.…”
Section: Faisabilité Du Traitement Des Tfo Par Laparoscopieunclassified